Synthesis of highly active and stable Pd/C catalysts toward HCOOH dehydrogenation by a simple NH3 adsorption method. (22nd October 2021) - Di, Lanbo; Wang, Hongyang; Zhang, Jingsen; Yu, Feng; Wang, Shengnan; Zhang, Xiuling
Abstract: Pd catalysts supported on activated carbon (Pd/C–NH3 ) toward HCOOH dehydrogenation were prepared by a simple adsorption method using ammonia (NH3 ) and Ar as the working gas. The results show that the TOFinitial of Pd/C–NH3 was 459.8 h −1  at 50 °C. When the reaction was carried out for 4 h, the HCOOH dehydrogenation ratio over Pd/C–NH3 was about 81.2%, which was 1.15 and 1.13 times, respectively, as that of the as-prepared Pd/C catalyst without any treatment (Pd/C–As) and the Pd/C catalyst purchased from Sigma-Aldrich (Pd/C-CM). The total amount of H2 and CO2 produced by using Pd/C–NH3 to decompose HCOOH in the third cycle was 99.4% of the gas produced by the first reaction cycle, and 1.80 and 12.60 times, respectively, as that of Pd/C–As and Pd/C-CM. The characterization results indicated that the Pd active species in Pd/C–NH3 migrated to the outer surface of the carbon support during the reaction, and the pore volume of the carbon support became larger, which were beneficial to the reaction. These factors made Pd/C–NH3 exhibit excellent HCOOH dehydrogenation activity and stability. NH3 adsorption is a simple and effective method for preparing high-performance Pd/C HCOOH dehydrogenation catalysts, and has important guiding significance for the preparation of other carbon supported noble metal catalysts. Graphical abstract: Image 1 Highlights: Pd/C–NH3 catalysts were fabricated by a facile ammonia adsorption method. Pd/C–NH3 exhibited superior activity and stability for HCOOH dehydrogenation. H2 generated over Pd/C–NH3 for the 1st and 3rd cycles were 1.13 and 12.60 times as that of Sigma-Aldrich. High performance is ascribed to the high Pd/C atomic ratio and the large pore volume.